PENGARUH KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. INDOJAYA AGRINUSA KABUPATEN KAMPAR - Nurhayati, Nurhayati (Jurnal Daya Saing, 2024)
This research is aimed at examining the effect of organizational commitment on employee job satisfaction at PT. Indojaya Agrinusa Kampar Regency organization on employee job satisfaction at PT. Indojaya Agrinusa, Kampar Regency. The sample obtained was 34 respondents in accordance with the research objectives. This research formulated a hypothesis for organizational analysis of employee job satisfaction at PT. Indojaya Agrinusa, Kampar Regency. To facilitate problem solving, this research was carried out using a simple linear regression analysis method with the help of SPSS Statistics version 25. Data was obtained from interviews and questionnaires using a simple linear regression formula with the formula: Y=a+Bx+e where Y= 18.647+ 0.893 X + e. The calculation results show that X represents the organizational commitment variable, giving a positive partial regression coefficient of 0.893 on the job satisfaction variable at PT. Indojaya Agrinusa, Kampar Regency. Measurements are carried out by calculating the coefficient of determination (R²) which is closer to 1, the more precise the linear line is. From the results of these calculations, an R² value of 30.4% of the employee job satisfaction variable in the production department at PT is obtained. Indojaya Agrinusa, Kampar Regency. determined by the independent variable, namely organizational commitment. Meanwhile, the remaining 69.6% is influenced by other variables.